Wien - Geschichte einer Stadt Band 2: Die frühneuzeitliche Residenz (16. bis 18. Jahrhundert) - Csendes, Peter (2003)
This volume is the second part of a trilogy on a detailed history of Vienna. It covers the period from the First Turkish Siege (1529) to the death of the Emperor Joseph II (1790). During these centuries the Habsburg dynasty and the court had been shaping predominantly the development of the city and the cultural townscape. In a detailed description fifteen authors give an overall view of the history of the constitution and administration, of the environmental, social, economic, and cultural development. Attention has been mainly focused on an analysis of the structural changes of the city's economy in the early modern period and the structure of the society, especially stressing its consequences in daily life. This historical description is based in many respects on the latest results of recent research. This volume provides the first concise history of Vienna between the 16th and 18th centuries in the last fifty years. It imparts the latest state of research to a wide public, supported by many illustrations and a large bibliography.